The usage of RPGS as an interdisciplinary method of teaching dyslexic students - Gatsakou, Christina; Bardis, Nikolaos; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The aim of this paper is to present a different viewpoint on the educational process through the usage of- adjusted to educational needs - RPGs (Role Playing Games), emphasizing on an interdisciplinary teaching in both cognitive and social-emotional level, which will offer intervention and simultaneously the improvement of the academic weaknesses for dyslexic students. RPGs -in any form- may be a powerful and unique teaching tool so that learning can be fun and meaningfully constructive to the dyslexic learners